2018
DOI: 10.1049/iet-nbt.2018.5117
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable green synthesis of silver nanoparticles by using Rangoon creeper leaves extract and their spectral analysis and anti‐bacterial studies

Abstract: The plant-based biological molecules possess exceptionally controlled assembling properties to make them suitable in the synthesis of metal nanoparticles. In the present study, an efficient simple one-pot method was employed for the synthesis of silver nanoparticles (SNPs) from the Rangoon creeper (RC) aqueous leaf extract. Biomolecules present in the leaf extract play a significant role as reducing agent as well as capping agent in the formation of RC-SNPs. The formation of RC-SNPs was confirmed by using seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The diversified applications of nanomaterials play an important role in day to day activities of human beings [1,2]. The nano sized materials are acting as bridge materials between macroscopic and microscopic materials with variety of functions [3]. Metal and metal oxide nanoparticles (MNPs & MONPs) have attracted many researchers for diversified applications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The diversified applications of nanomaterials play an important role in day to day activities of human beings [1,2]. The nano sized materials are acting as bridge materials between macroscopic and microscopic materials with variety of functions [3]. Metal and metal oxide nanoparticles (MNPs & MONPs) have attracted many researchers for diversified applications [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Of these, the peaks observed at 2h¼ 38.9 � , 45.7 � , 63.7 � , and 77.5 � belonged to the reflections from ( 111), (200), and (311) planes of AgNPs, respectively [22]. The other prominent peaks observed at 2h¼ 47.2 � , 55.4 � , and 66.6 � resulted from the reflections from (211), (220), and (222) planes of Ag 2 ONPs of the NCFs, respectively [22,23]. Thus, the NCFs had both in situ generated AgNPs and Ag 2 ONPs.…”
Section: Ftir Analysismentioning
confidence: 96%
“…In order to observe these additional low-intensity peaks, the diffractogram of the NCF prepared using 5 mM source solution was expanded in the 2h ¼ 35 � -80 � range and is presented in Figure 6(d). From Figure 6(d), it can be observed that there are many low-intensity peaks in the expanded diffractogram of which, the prominent ones at 2h¼ 38.9 � , 45.7 � , 47.2 � , 55.4 � , 63.7 � , 66.6 � , and 77.5 � belong to AgNPs and Ag 2 O nanoparticles (Ag 2 ONPs) [22,23]. Of these, the peaks observed at 2h¼ 38.9 � , 45.7 � , 63.7 � , and 77.5 � belonged to the reflections from ( 111), (200), and (311) planes of AgNPs, respectively [22].…”
Section: Ftir Analysismentioning
confidence: 99%
“…NMPs have been attractive applications in various fields including medical and pharmaceutical [1]. The earlier reports for the fabrication of NMPs used various plant extractions and transformation of bio‐materials; Prosopis Juliflora [2], Limonia acidissima [3], Tridax Procumbens [4], Moringa oleifera [5], Clerodendron serratum radix [6], Berberis vulgaris [7] and Terminalia Chebula [8]. The generation of nanomaterials is a part of bio‐nanotechnology by utilising bio‐molecules and other biodegradable polymers of plant materials.…”
Section: Introductionmentioning
confidence: 99%